أثر فعالية فرق العمل في إدارة الأزمات دراسةحالة كلية الإقتصاد جامعة الأغواط - إرامة بركة; مخنث منال; بن برطال عبد القادر (جامعة عمار ثليجي الاغواط, 2021)
This study aimed to shed light on the effectiveness of work teams in crisis management among the professors of the Faculty of Economics “University of Laghouat”. The study elements were determined by an independent variable represented in the effectiveness of work teams in five dimensions: (cooperation, participation, flexibility, sensitivity, facilitation). , and a dependent variable represented in crisis management, and to achieve this, a questionnaire was designed for the study and distributed to a random sample of (53) professors from the Faculty of Economics “Laghouat University” out of 104 professors, and the collected data were analyzed using the statistical program (SPSS v.25). And the use of the structural equations modeling method using the program (Smart PLS v.3), and this is to know the relationships between the studied variables and to determine the effects of the independent variable on the dependent variable. The results of the study showed that there is a statistically significant impact of the effectiveness of work teams on crisis management among the professors of the Faculty of Economics at the University of Laghouat at the moral level of 0.05, and this is through the presence of a statistically significant impact of participation on crisis management, while the rest of the dimensions (cooperation, flexibility, sensitivity, facilitation It did not have any statistically significant impact on crisis management.